2018
DOI: 10.1523/jneurosci.1219-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

A Posterior–Anterior Distinction between Scene Perception and Scene Construction in Human Medial Parietal Cortex

Abstract: Human retrosplenial complex (RSC), located in medial parietal cortex, has been implicated in numerous cognitive functions, including scene perception, spatial navigation, and autobiographical memory retrieval. Recently, a posterior-anterior distinction within RSC was proposed, such that posterior aspects process scene-related visual information (constituting a medial place area [MPA]), whereas anterior aspects process information that is vividly retrieved from memory, thereby supporting remembering and potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
47
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(63 citation statements)
references
References 75 publications
15
47
1
Order By: Relevance
“…4B). In the low-memory-error group the model predicted activity in a more anterior part, in the high-memory-error group in a more posterior part of the medial parietal lobe, akin to previous reports of an anterior-posterior functional distinction in this region (Silson et al, 2016(Silson et al, , 2019. Figure 4.…”
Section: Directional Tuning Reflects Spatial Memory Performancesupporting
confidence: 78%
See 1 more Smart Citation
“…4B). In the low-memory-error group the model predicted activity in a more anterior part, in the high-memory-error group in a more posterior part of the medial parietal lobe, akin to previous reports of an anterior-posterior functional distinction in this region (Silson et al, 2016(Silson et al, , 2019. Figure 4.…”
Section: Directional Tuning Reflects Spatial Memory Performancesupporting
confidence: 78%
“…Importantly, the medial parietal lobe, which comprises the RSC, is known for both its perceptual and mnemonic capacities (O'Craven and Kanwisher, 2000), which might be topologically distributed. Previous work revealed an anterior-posterior distinction for scene construction and scene perception (Epstein and Baker, 2019;Silson et al, 2016Silson et al, , 2019. Our results (Fig.…”
Section: Memory Retrieval and Learningsupporting
confidence: 65%
“…This finding was recently replicated and extended by another study that used recall of people and places and found the same posterior-anterior division between spatial and social processing (Silson et al, 2019a). In addition, comparison of scene viewing to other categories identifies the posterior region, retrosplenial complex, as scene-selective (Epstein, 2008;Epstein and Higgins, 2007;Silson et al, 2016Silson et al, , 2019b. The posterior-anterior division is supported by recent restingstate studies that divided the default-mode network into posterior and anterior components (Braga and Buckner, 2017;Braga et al, 2019).…”
Section: Discussionmentioning
confidence: 55%
“…Specifically, a small region of MPC directly anterior of scene-selective medial place area 7 (MPA) shows strong functional connectivity with anterior portions of scene-selective parahippocampal place area 18 (aPPA), located in medial VTC. This connectivity-defined region overlaps, qualitatively, with regions of MPC engaged during memory recall [2][3][4][5] , suggesting that the ventral/posterior aspect of MPC may contain distinct areas biased toward scene processing for vision and memory, respectively 19 .…”
Section: Main Textmentioning
confidence: 93%